Dynamic Secondary Borehole-Sealing Method for Gas Drainage Boreholes along the Coal Seam. (17th July 2018) - Qin, Wei; Xu, Jialin
Abstract : Under the influence of advanced abutment pressure, the tightness of a borehole is destroyed, so secondary borehole sealing is needed; however, the opportune time for a secondary borehole sealing is unclear. In addition, current borehole-sealing devices do not have a secondary borehole-sealing functionality. In this paper, an opportunity election model of secondary borehole sealing was established, and a dynamic secondary borehole-sealing device was developed. In working face 3908 of the Kaiyuan Coal Mine, an in situ dynamic secondary borehole-sealing test was conducted. The test results show that the tightness of the boreholes sealed with high-water-expansion slurry is obviously better than that of the boreholes sealed with cement mortar and polyurethane. When a borehole is destroyed by the peak of the advanced abutment pressure, the secondary borehole-sealing measures can significantly improve borehole suction pressure, gas concentration, and gas drainage amount in the advanced abutment pressure loading stage.